The Importance of Emotional Management in Ideological and Political Education for College Students - Yu, Haipeng (Journal of Theory and Practice of Management Science, 2023)
In the current era of rapid social development, college students not only face academic pressure, but also industry competition pressure when facing internship work. However, many college students' psychology is not yet mature, making it difficult to maintain a correct mindset when facing excessive pressure, which can easily lead to serious problems. As an important part of ideological and political education, emotional management is an effective content that can help college students control their emotions reasonably. This article conducts a systematic study on emotional management and provides several effective strategies to improve the ability to manage emotions, aiming to promote the healthy growth of more college students.